Psychometric Analysis of a Reduced Version of the Scale of Positive Affect and Negative Affect in University Students of Lima - Vásquez Vega, Jeanette (2023)
The objective of the study was to develop a short version of the Positive Affect and Negative Affect Scale (PANAS), from the original version of 20 items, proposed by Watson et al. (1988a). The sample consisted of 3960 students from a public university in Lima. The results indicate that the validity of the internal structure, through exploratory and confirmatory factor analysis, was defined by 10 items and two dimensions. Positive affects are organized into five items: determined, optimistic, inspired, active, and attentive; while negative affects are in five items: irritable, hostile, angry, guilty, and ashamed. Likewise, it was found for the final short version, standardized coefficients with factorial loads between .48 and .85, as well as the fit indices of the model were in accordance with what was expected. Internal consistency reliability indicates Alpha and Omega coefficients greater than .70 in both factors. It is concluded that the instrument presents evidence of internal structure and the scores are consistent.